Inovação em produtos para a base da pirâmide: Evidências em empresas brasileiras. - Lacerda, Katarina Chaves (2016)
The bottom of the pyramid market has attracted the attention of companies looking to expand their profit margins and gain competitive advantage. As this is a market with specific characteristics and needs, to innovate and meet these consumers it is necessary for companies to establish innovative strategies favorable to achieve success in this market. Moreover, the internal and external environment organizations has elements that can enable the innovation process, and consequently, the implementation of innovative strategies. In this sense, the objective of this research was to analyze how Brazilian companies have developed innovations in products for the base of the pyramid. Specifically, we sought to investigate the innovations introduced in the market to meet the bottom of the pyramid, describe the innovation strategies used and identify enablers of innovation to the base of the pyramid. A multiple case study as a methodological strategy was used, approaching three companies that direct products to this public. Data were collected by means of semi-structured interviews, direct observations and information obtained on the website for businesses, and others related to them and their innovations. Each case was held at first individually then crosses, based on the relevant categories to specific research objectives. The results showed that, to meet the bottom of the pyramid of consumers, enterprises have developed innovations in products, innovation processes and innovation in marketing, where such innovations are considered as new market disruptive. Multiple innovative strategies have been used for the implementation of innovations in the bottom of the pyramid market by the three companies, including the principal were like: market-based and exploitative. Among the enablers of innovation, the economy, the creation of knowledge and learning, and the recognition of the value and need for innovation were the most prevalent to facilitate the success of innovation for companies. It was concluded that the reality of the Brazilian market, to have a product innovation to the base of the pyramid it is necessary to perform other innovations, is to create this new product in the case of process innovation, is to support the implementation of this product on the market, by means of a marketing innovation; that innovation strategies used together contribute to organizations to achieve their innovative goals; and even acting in different sectors there is correspondence between the enablers of innovation of the companies analyzed.